Personal Health Information in Canada: Clearing the Conceptual Underbrush and Accounting for Public Opinion - Peekhaus, Wilhelm (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper explores the relationship between individuals and their medical information in Canada. It employs Neill’s theoretical model of privacy to situate Canadian legislation, and also analyzes public opinion data about attitudes toward medical and genetic privacy, indicating areas where legislation and public opinion are out of synch. Cet article examine la relation qui existe entre les individus et leurs renseignements médicaux au Canada. Le modèle théorique de Neill sur la confidentialité est utilisé pour situer la loi canadienne. Cet article analyse également les données tirées de l’opinion publique concernant les attitudes envers la confidentialité médicale et génétique et souligne des points où la loi et l’opinion publique ne sont pas synchronisées.